Digital Game-based Learning (DGBL) in the L2 Classroom: The Impact of the UN's Off-the-Shelf Videogame, Food Force, on Learner Affect and Vocabulary Retention - Hitosugi, Claire Ikumi; Schmidt, Matthew; Hayashi, Kentaro (CALICO journal, 2014)
This mixed-methods study explored the impact ofFood Force (FF), a UN-sponsored off-the-shelf videogame, on learner affect and vocabulary learning and retention in a Japanese as a second/foreign language classroom. The videogame was integrated into an existing curriculum and two studies were performed. In Study 1 (n= 9), new vocabulary was embedded in task sheets. Study 2 (n= 11) introducedFFvocabulary explicitly and included a graded unit test. In both studies, participants took threeFFvocabulary tests (pre-, post-, and delayed) and an end-of-unit affect survey. Study 2 also included textbook vocabulary tests and interviews. Results indicated positive impact on learner affect and a preference for game-mediated activities over conventional exercises. Within-subject repeated-measure analysis revealed that participants in both groups recalled newFFvocabulary five weeks later at the same rate as immediately after the unit, while they significantly forgot words from the textbook. Study 2 resulted in better learning ofFFwords than Study 1. No gender difference was found in vocabulary test results. PositiveFFeffects may be evidence that digital game-based learning facilitates deep learning. Though there was significant positive effect on average, individual differences were found in students' attitudes and vocabulary retention.